Flexing Charity on Social Media: A Thematic Qur'anic Study of Philanthropic Verses - Riska Nur Hidayati; Musholli Musholli (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2026)
The rapid development of social media has transformed philanthropy into highly visible digital self-presentation, giving rise to "charity flexing." While previous research examines this through Islamic law and ethics, comprehensive thematic (maudhu'i) analyses of philanthropic verses remain limited. This study aims to analyze the Qur'anic concept of philanthropy and its relevance to social media flexing. Employing a qualitative library research approach, this study utilizes the thematic interpretation method to collect and analyze verses related to zakat, infaq, sadaqah, and waqf (ZISWAF). The findings reveal that Qur'anic philanthropy is grounded in sincerity, social justice, public welfare, and solidarity. Furthermore, the ethical distinction between commendable digital philanthropy and problematic flexing lies in intention, motivation, and social impact. Publicly displaying charity can boost social awareness and transparency; however, it risks riya’ (ostentation) when driven by self-promotion. This study contributes an integrated ethical framework to understand digital philanthropy and online self-presentation, concluding that digital-era philanthropic practices must balance spiritual sincerity with social responsibility, supported by digital ethical literacy to prevent the normalization of performative charity.